Globalization, regulation and profitability of banks: A comparative analysis of Europe, United States, India and China - Elisabeth Paulet; Hareesh Mavoori (The European Journal of Comparative Economics (EJCE), 2019)
The last financial crisis spurred regulators to emphasize enhanced stability indicators for financial institutions. Therefore, banks have to take into account this new element while defining their strategic decisions and their profitability. The aim of this paper is to provide evidence of the transformation of banking activities on a global scale comparing different regulatory and governance regimes. Using a sample of 102 banks from 4 geographic regions (United States, Europe, China, India) we propose pooled and regional models to highlight the parameters that explain profitability and risk management of banks. Leveraging 2000-2016 monthly data, our empirical analysis underlines the regional differences in profitability, which influence global stability of banking institutions. We find that increasing market capitalization often induces increased performance as expected; however a regional analysis of its impact reveals more nuanced geospatial variations and insights for risk management purposes. In particular, China constitutes an interesting case study as regards the impact of government on the performance of banking institutions, with this effect being cross validated by models contrasting private and public sector banks with different levels of government controls.
Keywords: F65; G21; P5; 330; Regulation; Bank performance; Government intervention; Multiregional comparison; Risk management; Structural equation modeling